Implementation of Differentiated Learning in English Lesson Using Independent Curriculum at MAN Surabaya - Syafira Ahmad, Dinda; Hesmatantya, Vega; Mayasari, Linda (P3M Politeknik Negeri Jember, 2024)
This study explores differentiated learning in English classes at MAN Surabaya within the Independent Curriculum framework. Differentiated learning adapts teaching strategies, content, and assessments to meet students' varying needs, readiness levels, interests, and learning profiles. The research identifies strategies used by the teacher, student preferences, and implementation challenges. Using qualitative methods such as observations, interviews, and document analysis, the study finds that the teacher employs flexible grouping, tiered assignments, and individualized instruction to cater to diverse student needs. Students favor activities aligned with their interests and readiness, finding them more engaging and effective. However, challenges include limited resources, time constraints, and the need for ongoing professional development. The study concludes that differentiated learning can improve student engagement and achievement but requires significant support for the teacher, including resources, time for planning, and continuous professional development. These findings highlight the importance of educational policymakers and school administrators providing necessary support and resources to enable effective differentiated learning implementation in classrooms.